Psychological Foundation for the Development of the Foundation Phase Al-Quran Learning Curriculum - Martina Purnasari; Mulyawan Safwandi Nugraha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The Quran, which serves as a guide for Muslims, is the most important education that must be instilled from an early age. However, educators need to understand how to develop a curriculum that aligns with the psychological foundation in the Foundation Phase. Since the Foundation Phase is a crucial period in human life, neglecting it is equivalent to preparing a fragile generation. Therefore, the researcher focuses on observing and analyzing this aspect to ensure that learning is enjoyable and meaningful. This research aims to analyze the implementation of Quranic learning from the perspective of psychological foundations. The study utilizes a qualitative approach with a case study design, involving direct field research at the Islamic Kindergarten Plus Prima Insani. Data collection techniques include interviews, document analysis, and observation. Quranic learning in the Foundation Phase can be effectively implemented if it stays within the psychological foundation, significantly aiding in the psychological development of children and fostering noble religious values. This, in turn, contributes to the creation of individuals who have a positive impact on society.